Barriers to adaptive reasoning in community ecology - McLachlan, Athol J.; Ladle, Richard J. (Biological reviews of the Cambridge Philosophical Society, 2011)
Recent high‐profile calls for a more trait‐focused approach to community ecology have the potential to open up novel research areas, generate new insights and to transform community ecology into a more predictive science. However, a renewed emphasis on function and phenotype also requires a fundamental shift in approach and research philosophy within community ecology to more fully embrace evolutionary reasoning. Such a subject‐wise transformation will be difficult due to at least four factors: (1) the historical development of the academic discipline of ecology and its roots as a descriptive science; (2) the dominating role of the ecosystem concept in the driving of contemporary ecological thought; (3) the practical difficulties associated with defining and identifying (phenotypic) adaptations, and; (4) scaling effects in ecology; the difficulty of teasing apart the overlapping and shifting hierarchical processes that generate the observed environment‐trait correlations in nature. We argue that the ability to predict future ecological conditions through a sufficient understanding of ecological processes will not be achieved without the placement of the concept of adaptation at the centre of ecology, with influence radiating outwards through all the related (and rapidly specializing) sub‐disciplines.